Green nanotechnology synthesized silver nanoparticles: Characterization and testing its antibacterial activity - AlMasoud Najla (De Gruyter, 2021)
The green plant-mediated synthesis of silver (GPS-Ag) nanoparticles (NPs) has been increasingly popular due to its eco-friendliness, availability, cost-effectiveness, and the fact that it can be safely handled and possesses a broad variability of metabolites, such as antioxidant and antimicrobial activities. In this current study, the synthesis of AgNPs has been demonstrated using aqueous extracts of fresh leaves of Ficus carica and Salvia rosmarinus (rosemary) that reduced aqueous silver nitrate. This procedure made the synthesis of NPs possible, which was characterized by numerous analytical techniques such as ultraviolet-visible (UV-Vis) spectrophotometry, Fourier transform infrared spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy, and dynamic light scattering studies. The visual observation indicated that the colour of aqueous silver nitrate turned brownish yellow after treatment with the fresh leaf extracts and was confirmed by UV-Vis spectra. In addition, the TEM analysis showed that the synthesized NPs well dispersed with average sizes less than 22 nm. Furthermore, AgNPs and aqueous leaf extracts of F. carica and rosemary were examined for their antimicrobial activities against different Gram-positive and Gram-negative bacteria strains. The results indicated that the AgNPs, derived from F. carica, have more antibacterial activities than others and inhibited bacterial growth.